Sources of genetic resistance to Fusarium wilt (Fusarium oxysporum f. sp tracheiphilum) in cowpea (Vigna unguiculata (L.) Walp.) and comparison of inoculum concentration levels - Omoigui, L.O.; Danmaigona, C.C.; Kamara, A.Y.; Alakonya, A.E.; Ademulegun, T.D.; Zarafi, A.B. (Informa UK Limited, 2023)
Fusarium wilt caused by Fusarium oxysporum f. sp tracheiphilum (Fot) is a soil-borne fungal disease of significant constraint to cowpea production in West Africa. The disease infection can cause up to 100% yield loss in highly infested fields. The most effective control strategy is the use of resistant varieties. Sixty cowpea germplasm collections were screened for resistance to F. oxysporum. The result revealed that only two (TVu 134 and TVu 410) of the germplasm showed a high level of resistance when subjected to artificial epiphytotic and innovative seedling root dip screening methods using three inoculum concentration levels. These two cultivars can be used directly by farmers or as potential donors for developing resistant cultivars against F. oxysporum. The study also identified useful polymorphic SSR markers associated with resistant and susceptible parents, which will significantly enhance the breeding programs in developing varieties’ resistance to the disease.